從香港數學課程發展的歷史經驗透視當前課程發展與決策的幾個問題 - 黃毅英Ngai-Ying Wong; 顏明仁Ming-Yan Ngan; 霍秉坤Ping-Kwan Fok; 鄧國俊Kwok-Chun Tang; 黃家樂Ka-Lok Wong (Higher Education Foundation, 2009)
小學數學課程自1960年代起經歷數次改革，其中涉及不少課程轉型，包括由技巧轉向能力、著重知識（數學）結構、強調操練轉至強調動手探索、改良評核模式等。回顧這一段漫長的改革路，「p（product-結果）和p（process-過程）」的對立，學科與跨學科學習的爭持（所謂打破學科藩籬），課程規劃與專業發展的張力及規範與自由的平衡等問題在歷史上似乎在不斷重演，本文欲以數學課程發展的歷史為鑑，透視當前課程發展與決策的問題。探討發現數學科面對的課程轉向，出現於中文、通識、中國歷史等科；而數學課程發展引起的爭論，也出現於其他各科。當局決定課程時，若未能借鑑歷史發展，相類問題仍會持續不斷。 Since 1960, primary and secondary mathematics curricula changed several times in Hong Kong. Throughout these changes, the curriculum approach shifted from techniques to generic skills, emphasizing knowledge (mathematics) structure, transforming from drilling to hands- on inquiry, modifying assessment mode, etc. Reviewing this long and wandering reform, the history repeats itself in various aspects such as the conflict of product and process, argument between disciplinary and cross-disciplinary learning, tension among curriculum development and professional development and the balance of regulating and freedom. This article aims, learning from the historical development of mathematics curriculum, to review the recent development and decision of curriculum. This review finds that curriculum changes in mathematics are appearing in other subjects like Chinese Language, Liberal Studies and Chinese History. Moreover, the debates arising out of mathematics curriculum development also emerged themselves in other subjects areas. When making curriculum decisions, similar problems will continue to occur if we cannot learn lessons from history.